les Droits humains sont-ils universels ? - Simone ZURBUCHEN (Journal international de bioéthique et d’éthique des sciences, 2010)
It is often held that the universality of human rights can best be defended on the basis of the idea of an “overlapping consensus”. This paper contends that some of the most prominent philosophical human rights conceptions that have recently been proposed (“basis-driven” conceptions) cannot be reconciled with this idea. It is however possible to sketch an alternative strategy for defending the universality of human rights